TEACHER-STUDENT INTERACTION IN A PROJECT-BASED LEARNING CLASSROOM - Muhammad Ilyas Nasruloh (Journal of English and Education, 2013)
This paper reports on a study aiming at investigating the realization of teacher-student interaction during the implementation of Project-Based Learning approach. The data in the form of observations, interviews, and video transcripts were taken from an elementary school English teacher and 30 fifth grade students in a private school in Bandung. The findings reveal that Teacher Talk took a greater proportion than Pupil Talk throughout the interaction. If it is compared with traditional method, Project-Based Learning did not give significant changes in overall percentage. However, Project-Based Learning relatively gives a major contribution especially to the characteristics of teacher-student interaction. Keywords:Young learners, elementary school, teacher-student interaction, speaking strategies, project-based learning approach